Reflecting Religious Truth from the Interpretation of the Kingdom of God: An Analysis of Philosophical Hermeneutics of Paul Ricoeur in Luke 17:20-36 - Purwadi, Y. Slamet (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2013)
‘The Kingdom of God’ reflects a hidden truth that needs to be probed, disclosed and exposed to achieve its true meaning. It portrays significant as well as controversial theme in the Gospel and triggers multi interpretations. This paper investigates how philosophical hermeneutics of Paul Ricoeur can be applied on the issue of religious truth of the Kingdom of God. The significance of Ricoeur's hermeneutics lies precisely in the process when interpretation is brought 'in front of text' involving the world of interpreters and the subjectivity of the readers, namely the urgency of Kingdom as a project of faith in contemporary world or, phenomenologically, the project that involves our being as being-in-the-world. The truth of the Kingdom of God is examined through the method of Ricoeur's hermeneutic circle following dynamical levels or moments of understanding: pre-critical, phenomenological-critical and existential-post-critical. The primacy of language in Ricoeur's hermeneutics places the power of linguistic re-description; it becomes crucial in correlating the Kingdom of God as text and event. Linguistic re-descriptive power helps articulate the so-called dimensions of impossible demand in biblical hermeneutics. It reflects the inexhaustability and irreducibility of the Kingdom's inspirational power both in linguistics itself and its expressions as an action.